An exploratory study of human rights knowledge: a sample of Kindergarten and elementary school pre-service teachers in Spain - Messina, Claudia (Human rights review, 2013)
This study aims to explore the level of information and knowledge 150 Spanish kindergarten and elementary school teachers in pre-service training have about human rights. We compared two groups of students: students with no specific training and students with specific training (the students with specific training study with the new training teaching programme that includes a compulsory subject related to citizenship education). The contents are organized around three thematic areas. Human rights are included in the first area ‘Basic concepts to promote equality and participation in Elementary Education’; the other two areas are: ‘Learning to participate at Elementary School’ and ‘Building a civil school that promotes equality and participation at Elementary School’. It is a one semester subject with 3 h of teaching per week. The main hypothesis is that a specific training on human rights will lead to an important improvement not only in student’s level of knowledge but also in the way they categorize this specific content. We have administered a questionnaire designed for the study. In general, our results show that students of both groups have a basic and limited knowledge about human rights. The group with specific training shows a higher level of knowledge than the other group and a different way of organizing it. This would go in the direction of other studies of supporting and reinforcing the inclusion of specific training on human rights during the initial teacher training programmes at the university.